Budaya Leles pada Masyarakat Manggarai sebagai Fenomena Sosial dalam Terang Etika Deontologi Immanuel Kant - Martinus Celi Ambo; Paskalis Aldo Mastiko; Profasius Samuel Lembak; Kristianus Adrianto Virando (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
The leles culture in Manggarai society is a complex phenomenon that significantly impacts social cohesion. Using Immanuel Kant’s deontological ethics, this study examines how leles can be understood within the context of moral obligation. This research employs a qualitative-descriptive method to understand the issues surrounding leles culture in Manggarai society. Data were collected from scientific books, journals, and interviews. Field findings indicate that leles culture has shifted due to the spread of modern technology in Manggarai, resulting in a decline in the values of cooperation and togetherness. In fact, leles is a cultural product and ancestral heritage. Therefore, this study analyzes the implications of Kant’s philosophy for leles culture amid declining social cooperation. Using Kant’s ethical approach, the author proposes three points to revive leles: first, integration of ethical awareness with leles practice; second, education and value awareness; third, community development. These three points serve to raise awareness of technology’s impact on culture and social cooperation. This study does not intend to examine the entire Manggarai community nor analyze social phenomena generally as in sociology, but emphasizes the social aspects of leles culture as material for critical reflection.